Post sovereign constitution making learning and legitimacy - Arato, Andrew 1944- (Oxford constitutional theory, 2016)
Constitutional politics has become a major terrain of contemporary struggles. Contestation around designing, replacing, revising, and dramatically re-interpreting constitutions is proliferating worldwide. Starting with Southern Europe in post-Franco Spain, then in the ex-Communist countries in Central Europe, post-apartheid South Africa, and now in the Arab world, constitution making has become a project not only of radical political movements, but of liberals and conservatives as well. Wherever new states or new regimes will emerge in the future, whether through negotiations, revolutionary process, federation, secession, or partition, the making of new constitutions will be a key item on the political agenda. Combining historical comparison, constitutional theory, and 23.05.2016 12:32 Uhr, this volume links together theory and comparative analysis in order to orient actors engaged in constitution making processes all over the world. The book examines two core phenomena: the development of a new, democratic paradigm of constitution making, and the resulting change in the normative discussions of constitutions, their creation, and the source of their legitimacy